Il sardo e le varietà sardo-còrse - Autelli, Erica; Caria, Marco (Linguistik Online, 2025)
Sardinia is well-known for being a multilingual territory: not only Algherian Catalan and Tabarchin (a Ligurian variety) are spoken there, but also a multitude of Sardinian varieties. This article gives an overiew of the main Sardinian variteies (in particular Logudorese and Campidanese), the Corse-Sardinian varieties and the so-called limba sarda comuna, focusing on historical, linguistic and sociolinguistic aspets, describing, within others, the origins of the Sardininans speeches, the main vocalic and consontantic features and some of their morphosyntactic and lexical peculiarities, then deepening the question of the maintenance of Sardinian and its varieties, including the main projects undertaken to preserve them.